1991
DOI: 10.1159/000235502
|View full text |Cite
|
Sign up to set email alerts
|

16-Kilodalton Rice Protein Is One of the Major Allergens in Rice Grain Extract and Responsible for Cross-Allergenicity between Cereal Grains in the Poaceae Family

Abstract: Cross-allergenicity between five cereal grains including rice, wheat, corn, Japanese millet (Panicum crus-galli L. var. frumentaceum Trin.) and Italian millet (Setaria italica Beauv. var. germanica schrad.) was examined by radioallergosorbent test (RAST) and RAST inhibition assay. There were significant close correlations between every combinations of RAST values for the five cereal grain extracts. RAST inhibition assay of each extract against RAST discs coupled with other cereal grain extracts indicated marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 16 publications
2
46
0
1
Order By: Relevance
“…However, it is still uncertain whether such 'hypo-allergenic rice' seeds obtained from the transgenic rice plants are tolerable to patients allergic to rice, because even a small amount of residual allergens could elicit an allergic reaction in patients. Furthermore, some patients have been reported to be allergic to some other components of rice seed proteins [6]. Further studies on the improvement of the antisense allergen genes and identification of the other allergenic proteins and their genes are in progress.…”
Section: Y Tada Et Al/febs Letters 391 (1996) 341-345mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still uncertain whether such 'hypo-allergenic rice' seeds obtained from the transgenic rice plants are tolerable to patients allergic to rice, because even a small amount of residual allergens could elicit an allergic reaction in patients. Furthermore, some patients have been reported to be allergic to some other components of rice seed proteins [6]. Further studies on the improvement of the antisense allergen genes and identification of the other allergenic proteins and their genes are in progress.…”
Section: Y Tada Et Al/febs Letters 391 (1996) 341-345mentioning
confidence: 99%
“…Several studies on allergic reaction to rice have indicated that patients' sera contain immunoglobulin E (IgE) reacting to rice proteins, and that soluble proteins, albumins and globulins have a high degree of allergenic activity [3,4]. The authors have isolated a rice seed protein of about 16 kDa with reactivity for IgE of several rice-allergic patients [5], and the 16 kDa protein was later identified as one of the major allergens in rice seed [6]. Monoclonal and polyclonal antibodies raised against the 16 kDa allergen were shown to cross-react with the 14--16 kDa allergens [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several rice proteins with molecular masses of 9, 14-16, 26, 33 and 60 kDa have so far been reported to be recognized by the serum IgE of patients showing hypersensitive reactions to rice ingestion. These rice allergens have been identified as non-specific lipid transfer protein-1 (nsLTP1), 29) -amylase/trypsin inhibitors, 25) -globulin, 30) glyoxalase I (GlyI) 24) and granule-bound starch synthetase (GBSSI). 26) Most of these allergens have been used to assess the safety of GM rice.…”
mentioning
confidence: 99%
“…Among rice proteins, 16 kD protein has been known as one of the major allergens in rice grain, and it also inhibits serum IgE binding to other cereal grain extracts including wheat, corn and millet (Urisu et al, 1991). These rice allergenic proteins are rice seed albumin and exhibit microheterogeneity in molecular weight (14-16 kD) (Matsuda et al, 1991).…”
Section: Introductionmentioning
confidence: 99%